Improving skills development in the informal sector : strategies for Sub-Saharan Africa - Adams, Arvil V. (Directions in development (Washington, D.C.). Human development., 2013)
The informal sector of Sub-Saharan Africa is comprised of small and household enterprises that operate in the non-farm sector outside the protected employment of the formal wage sector. The sector was identified 40 years ago by the ILO representing a pool of surplus labor that was expected to be absorbed by future industrialization, but rather than gradually disappearing, it has become a persistent feature of the region's economic landscape accounting for a majority of jobs created off the farm. Acknowledging its potential as a source of employment for the region's expanding workforce and impr.